The Effect of Total Quality Management and Work Motivation on Employee Performance at Cv. Pelangi Mitra Bandar Lampung - Ghaniyy, Arrafi; Efriyanti, Farida (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study aims to test employee performance at CV. Pelangi Mitra Bandar Lampung which is influenced by TQM and work motivation both individually and simultaneously. This research has a quantitative approach. The employee population owned by CV. Pelangi Mitra Bandar Lampung is 30 people which is called a saturated sample. Furthermore, questionnaires were distributed and the results were tested using SPSS 27 software with multiple linear tests. The results of this study, employee performance at CV. Pelangi Mitra Bandar Lampung is positively and significantly influenced by work motivation and overall quality management. Based on the results of the study, increasing employee work motivation and overall quality management implementation standards will directly increase productivity. This means that optimal employee performance will help achieve overall organizational goals if TQM and work motivation are implemented properly.